A survey on design challenges of scheduling algorithms for wireless networks. (8th April 2022) - Malekpourshahraki, Mojtaba; Desiniotis, Christopher; Radi, Marjan; Dezfouli, Behnam
Recent advances in wireless technologies open up new avenues toward many newer applications; however, existing wireless networks are not efficient enough to satisfy some new applications' requirements such as low energy consumption, high throughput, and low end-to-end delay. Scheduling algorithms are promising for performance improvement by addressing the limitations of standard networking protocols. Due to the widespread deployment and applications of wireless networks, a significant number of scheduling algorithms has been proposed to improve network performance. In this paper, we provide a systematic comparison among proposed scheduling algorithm with an exhaustive, network-independent framework to easethe comparison among different scheduler design and highlight important challenges in the term of algorithmic parameters, computational order, accuracy, and overhead. We also study a set of schedulers in two main categories: low-power, and high-throughput, concerning our framework to extract the weakness and strength of each proposed method compared to other scheduling algorithms.